Throwing the rascals out?: the electoral effects of corruption allegations and corruption scandals in Europe 1981-2011 - Bågenholm, Andreas (Crime, law and social change, 2013)
Corrupt politicians have to a surprisingly great extent been found to go unpunished by the electorate. These findings are, however, drawn from case studies on a limited number of countries. This study, on the contrary, is based on a unique dataset from 215 parliamentary election campaigns in 32 European countries between 1981 and 2011, from which the electoral effects of corruption allegations and corruption scandals are analyzed. Information about the extent to which corruption allegations and scandals have occurred is gathered from election reports in several political science journals, and the electoral effects are measured in terms of the electoral performances - the difference in the share of votes between two elections - of all parties in government, as well as the main incumbent party, and the extent to which the governments survive the election. The control variables are GDP growth and unemployment rate the year preceding the election, the effective number of parliamentary and electoral parties, and the level of corruption. The results show that both corruption allegation and corruption scandals are significantly correlated with governmental performances on a bivariate basis; however, not with governmental change. When controlling for other factors, only corruption allegation has an independent effect on government performances. The study thus concludes - in line with previous research - that voters actually punish corrupt politicians, but to a quite limited extent.